Collaborative action research to reduce persistently long patient wait times in two public clinics in Western Cape, South Africa - Dr. A Sastry, PhD; K N G Long, MSPH; A de Sa, MBChB; H Salie, MBChB; S Topp, PhD; S Sanghvi, MBA; L van Niekerk, MBChB (Elsevier, 2015)
Background: Lengthy waiting times are problematic for patients and health-care workers alike. In clinics and hospitals across Africa, persistently long wait times have been linked to poor medication compliance, skipped appointments, delayed implementation of clinical programmes, and low healthcare worker morale. This collabortiave action research study explores practical methods to reduce patient waiting time in high-volume urban primary care public health facilities in South Africa. Methods: This study took place in three phases between November, 2013, and July, 2014, in two public-sector primary care clinics in Cape Town, South Africa. Clinic A had an average of 1800 patients per month and aimed to reduce waiting times in the pharmacy. Clinic B saw 1300 patients per month and sought waiting time reductions in all departments. The study team included clinic leaders and frontline staff, South African and US researchers, and graduate business students from the Global Health Lab at MIT Sloan School of Management. During phase one, collaboration members used discussions and site visits to define clinic processes, understand patient visit patterns, and identify bottlenecks using baseline waiting time data and observation. In phase two, students and researchers worked with staff at the clinics to develop readily implementable operational improvements to address bottlenecks. In phase three, clinic leaders and frontline staff maintained many changes, and also generated and tested new ideas to reduce patient wait time. We recorded waiting times at both facilities in phases one and three and used t tests to compare them. Findings: In clinic A, mean pharmacy waiting time was reduced from 129 min (median 86 min) to 102 mins (52 min; p <0·0001). In clinic B, mean wait times fell from 275 min (median 256 min) to 196 min (161 min; p <0·0001). To achieve these reductions, clinics made operational changes that included procedural improvements, software adjustments, and customisation of processes by type of patient visit. These functional changes were enabled by the engagement of clinic leadership, the team's past experience with improvement collaborations, and the joint development of targeted and locally-appropriate solutions that drew on staff ideas and capabilies. Barriers to success included staff turnover, fatigue from adapting to new requirements, and resource constraints. Interpretation: Waiting times in busy primary care facilities are influenced by many structural and relational factors. Amid this complexity, the action research collaboration demonstrated that simple changes generated in situ can help address the vexing challenge of persistent lengthy wait times and trigger further functional changes. Although follow-on research is needed to assess ongoing sustainability and broader applicability, our findings reveal the promise of short-term, inclusive collaboration involving frontline health workers, facility leadership, and targeted external support to bring about beneficial change. Funding: This study used resources contributed by the research team and Global Health Lab, MIT Sloan School of Management.